2017
DOI: 10.1038/eye.2017.243
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative optical coherence tomography to evaluate the effect of the eyelid speculum on corneal pachymetry during accelerated corneal cross-linking (9 mW/cm2)

Abstract: PurposeTo investigate intraoperative anterior segment optical coherence tomography (AS-OCT) to compare pachymetry changes between two methods (group 1: speculum-on, group 2: speculum-off during riboflavin instillation stage) during corneal cross-linking /CXL) (9 mW/cm for 10 min) in keratoconic patients.MethodsIn this interventional case series, 11 eyes (11 patients) in group 1 and 14 eyes (14 patients) in group 2 were enrolled. Pachymetry measurements by spectral domain OCT was performed at baseline, after ep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…As shown in the Figures 1 and 2, the speculum-off group had a more stable corneal pachymetry value during riboflavin instillation. On the other hand, the speculum-off group had a greater decrease in the corneal pachymetry value during the irradiation phase, further highlighting the limitations imposed by corneal stromal shrinkage using the isotonic dextran containing riboflavin solution for CXL [25].…”
Section: Application Of Intraoperative Oct For Monitoring Corneal Pacmentioning
confidence: 93%
“…As shown in the Figures 1 and 2, the speculum-off group had a more stable corneal pachymetry value during riboflavin instillation. On the other hand, the speculum-off group had a greater decrease in the corneal pachymetry value during the irradiation phase, further highlighting the limitations imposed by corneal stromal shrinkage using the isotonic dextran containing riboflavin solution for CXL [25].…”
Section: Application Of Intraoperative Oct For Monitoring Corneal Pacmentioning
confidence: 93%
“…Several studies reported successful use of OCT to measure corneal thickness and/or corneal dissection depth during CXL and refractive surgery [94,95]. Compared to the current gold standard for measuring corneal thickness, ultrasound pachymetry, OCT pachymetry has several advantages.…”
Section: Corneal Crosslinking and Refractive Surgerymentioning
confidence: 99%
“…Mazzotta and Caragiuli [ 60 ] reported the use of i OCT during corneal cross-linking and recommended intraoperative optical pachymetry evaluation before starting UV-A irradiation. Ghaffari et al [ 61 ] and Pahuja et al [ 62 ] also reported the use of i OCT or MIOCT during corneal cross-linking to evaluate the corneal pachymetry during the surgery. Kobayashi et al [ 63 ] used MIOCT not for surgery but for evaluation of donor cornea tissues through the viewing chamber.…”
Section: Other Applicationsmentioning
confidence: 99%